2022
DOI: 10.1128/spectrum.02595-22
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Early Prediction of Lymphoma Using High-Throughput Clonality Analysis of Bovine Leukemia Virus-Infected Cells

Abstract: Bovine leukemia virus (BLV) infection causes aggressive B-cell lymphoma in cattle and sheep. The virus has spread to farms around the world, causing significant economic damage to the livestock industry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A scheme for somatic mutation analysis in cattle with EBL development. Thirty-six EBL cattle collected in previous studies [37, 38] were used for the mutation analysis. Blood and tumor samples derived from the same EBL cases were examined to identify variants in their genome using amplicon sequencing that targeted 21 cancer-related genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A scheme for somatic mutation analysis in cattle with EBL development. Thirty-six EBL cattle collected in previous studies [37, 38] were used for the mutation analysis. Blood and tumor samples derived from the same EBL cases were examined to identify variants in their genome using amplicon sequencing that targeted 21 cancer-related genes.…”
Section: Resultsmentioning
confidence: 99%
“…The information on EBL cases used in this study are listed in Table S1. All cases were diagnosed as EBL in a domestic livestock hygiene service center and meat inspection center in Japan, and they were kindly provided for research use in the previous studies [37, 38]. To select EBL cases not showing leukemic signs, it was confirmed that lymphocyte counts or clonality values measured by the RAISING-CLOVA method [38] were low in the blood (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new method called RAISING-CLOVA has recently been proposed to be useful for the early prediction of EBL onset [ 23 ]. This method was used to analyze the clonality of BLV-infected cells (Cv) in 4 sheep with experimental BLV infection and showed that Cv increased before or at the EBL onset.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the risk of developing EBL by PVL alone is challenging, although PVL can be a rough index. Combination with other hematological markers or measures, such as clonality analysis of BLV-infected cells [ 21 ], which cannot readily perform in the field, would be needed for reliable diagnosis of EBL cattle. The negative binomial regression model built in this study suggested a correlation between MNT and PVL, consistent with other studies [ 17 ].…”
Section: Discussionmentioning
confidence: 99%